Effects of a dynamic foot movement device on cognitive performance in short-duration computer-based tasks. (September 2018) - Kar, Gourab; Sun, Yilu; Celikors, Elif; Villacreces, Paulina; Misailedes, Elena; Schatz, Marty; Kim, Jeyon; Shi, Yuan Ling Zi; Gao, Yitong; Sun, Joey; Zhang, Jiaming; Hedge, Alan
This pilot study compared cognitive performance in short-duration computer-based tasks between static sitting as control, and active sitting with use of a dynamic foot movement device as intervention. Using a within-subjects counterbalanced design; participants performed four computer-based tasks evaluating cognitive performance. A survey reported subjective evaluations of concentration, productivity, comfort, satisfaction, and preference for future use. Results from Digit span, Fitts' Spiral, Stroop and Typing tests indicate no significant difference in cognitive performance between intervention and control. Survey results suggest that 40% of participants expressed satisfaction and preference for future use of the intervention. In conclusion, findings from this study suggest that compared to static sitting, cognitive performance on short-duration computer tasks is not reduced with use of a dynamic foot movement device. The adoption of dynamic foot movement devices can potentially increase low-intensity concurrent physical activity without negatively impacting cognitive performance in short-duration computer-based office tasks.